Efecto de niveles de nutrición edáfica y foliar en la incidencia del daño del barrenador del tallo (Diatraea saccharalis) en el cultivo de arroz en la zona de Babahoyo - Mera Lizondo, Ramón Vicente (2016)
SUMMARY The work was carried out in the lands of the experimental farm of the Ability of Agricultural Sciences of the Technical University of Babahoyo, located in Km. 7,5 of the road Babahoyo-Montalvo. Ten treatments and three repetitions were investigated. The objective of this investigation was to evaluate the agronomic behavior of the cultivation of rice in front of the application of levels of nutrition soil and to foliate; to determine the most influential nutritious level about the incidence of barrenador of the shaft in rice and to establish the populational levels of Diatraea saccharalis of rice in front of the applied treatments. He was carried out the siembra of rice variety INIAP-16 in parcels of 20 m2. The treatments were distributed at random in a design of complete blocks in factorial arrangement. For the evaluation of stockings the test was used from Tukey to 5 % significance. At the end of the cycle of the cultivation height of plants, plaints number for m2 was evaluated, grains for panicule, longitude and number of panicule m2, days to flowering, days to crop, number of grains for panicule, weight 1000 seeds and yield for hectare, numbers of affected plaint and percentage of damage. The results determined that agronomic characteristic lLas of plant height, macollos number and panicule/m2, panicule longitude and grains for panicule presented good results applying N-P-K-Mg-S in dose of 120-20-70-20-30 kg/ha interaccionado with the use of Fertiestim 0,50 L/ha. The biggest yield in the cultivation (6264,6 kg/ha) it was obtained applying N-P-K-Mg-S in dose of 120-20-70-20-30 kg/ha with the use of Fertiestim 0,75 L/ha. The Witness conventional in dose of 69-0-60 kg/ha with Fertiestim in dose of 0,50 and 0,75 L/ha reached bigger percentage of damage.